Characterization of non-stoichiometric Ga2O3-x thin films grown by radio-frequency powder sputtering. Issue 3 (1st February 2021) - Cha, Su Yeon; Kim, Dongwoo; Lim, Hojoon; Mun, Bongjin Simon; Noh, Do Young; Kang, Hyon Chol
Abstract: We report the synthesis and characterization of non-stoichiometric Ga2 O3-x thin films deposited on sapphire (0001) substrates by radio-frequency powder sputtering. The chemical and electronic states of the non-stoichiometric Ga2 O3-x thin films were investigated. By sputtering in an Ar atmosphere, the as-grown thin films become non-stoichiometric Ga2 O2.7, due to the difference in sputtering yield between Ga and O species of the Ga2 O3 target. The electronic states of the thin films consist of ~85% Ga 3+ and ~15% Ga 1+, corresponding to Ga2 O3 and Ga2 O, respectively. The films have the electrical characteristics of a semiconductor, with electrical conductivity of approximately 5.0 × 10 -4  S cm -1 and a carrier concentration of 4.5 × 10 14  cm -3  at 300 K.